Awake craniotomy in Intraoperative magnetic resonance suite (IMRIS) setting: Our institutional experience - Bhave, Chinmaya Pradeep; Gandhe, Rajashree Uday (Indian Journal of Case Reports, 2020)
Neurosurgery of the lesions within or near eloquent areas of the brain is challenging due to the risk of causing permanent neurological deficits during resection. Awake craniotomy allows intraoperative monitoring of the brain functions and guides the neurosurgeon continuously in maximum safe resection of lesions near the eloquent cortex with minimum neurological deficit. Intraoperative magnetic resonance imaging (iMRI) helps the neurosurgeon in improving the safety and efficacy during resection of the lesions. The combination of awake craniotomy and iMRI increases the overall challenges for both neurosurgeons and neuroanesthesiologists and requires close communication between all the teams involved. We present a series of ten cases of awake craniotomy done in the iMRI suite for the resection of gliomas located in close proximity to functionally eloquent areas of the brain.